The dual status of cognitive psychology: as an approach and as area research - Meza Borja, Anibal (2005)
Psychology is defined and levels of behavior organization are proposed. After defining and featuring the psychological approach, behavioral approach is outlined and a broad resentation of cognitive psychology is offered with special emphasis on taxonomy of mental events and its main current orientations. Finally, general features of cognitive psychology are presented.